Regional haze in Wisconsin: sources and the spatial distribution. Issue 3 (3rd May 2004) - Schauer, James J; Rodger, Bruce; Kerr, Sara C
Abstract : The atmospheric fine particulate matter (PM2.5 ) chemical composition and the light scattering coefficient were measured at a rural air monitoring site in Wisconsin between September 2001 and August 2002 to understand the source of regional haze in the area. The average fine particle mass concentration, was 10.8 μg/m 3 over this time period and was 27.2% organic material, 2.4% elemental carbon, 34.2% ammonium sulfate, 31.6% ammonium nitrate, 3.7% soil, and 1.8% non-soil trace elements. Ammonium sulfate, organic matter, and soil were highest during the summer period while ammonium nitrate was highest during the winter. Elemental carbon peaked in the fall while the trace elements did not vary significantly. These trends were also observed at an urban Milwaukee site. A comparison of spring 2002 data between sites distributed across Wisconsin revealed a similar relative chemical composition, though absolute concentrations varied significantly. The average measured light scattering coefficient ( b sp ) at the rural sampling site was 53 ± 1 Mm −1 . The PM2.5 mass and the measured b sp showed good correlation with an R 2 of 0.84. The average chemical composition of the particulate matter was used to calculate b sp and the resulting values agree well with the measured b sp, though not as well as the PM2.5 mass, giving a regression slope of 1.06 and an R 2 of 0.72.